2012
DOI: 10.21848/audiol.2012.8.1.101
|View full text |Cite
|
Sign up to set email alerts
|

A study of the Speech and Environmental Sound Recognition in the Classroom Noise for School-aged Children with Hearing Loss

Abstract: This study aimed to measure accuracy of speech (monosyllables and sentences) and environmental sound recognition in the children with hearing aids (HA, N = 17) or cochlear implants (CI, N = 22) when listening in the classroom noise. Nine normal-hearing children participated as a control group. The classroom noise was recorded either just right before the class or during the break time. All the target sounds were presented at 65 dB SPL, and 5 dB signal-to-noise ratio was used between the target and noise sounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Only one study (Kim and Lee, 2012 ) examined ESI in the presence of background noise, using a fixed 5 dB signal-to-noise ratio (SNR) and two types of classroom noises recorded either before the class begins or during the break period. In all other studies, environmental sounds were always presented in quiet.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only one study (Kim and Lee, 2012 ) examined ESI in the presence of background noise, using a fixed 5 dB signal-to-noise ratio (SNR) and two types of classroom noises recorded either before the class begins or during the break period. In all other studies, environmental sounds were always presented in quiet.…”
Section: Resultsmentioning
confidence: 99%
“…For post-lingual adults, identification accuracy ranged between ~33% correct (Strelnikov et al, 2018 ) and 87.5% correct (Kaga and Akamasu, 2009 ). For children with CIs, two studies reported sound identification accuracy of 31.6 and 35.3% (Kim and Lee, 2012 ; Berland et al, 2019 ), while a third study reported 67.6% accuracy (Liu et al, 2013 ). The single study, which focused specifically on pre/perilingual late-implanted adults, reported identification accuracy of 40.5% (Peasgood et al, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations